Fatty acid synthesis is critical for stem cell pluripotency via promoting mitochondrial fission. (4th April 2017) - Wang, Lihua; Zhang, Tong; Wang, Lin; Cai, Yongping; Zhong, Xiuying; He, Xiaoping; Hu, Lan; Tian, Shengya; Wu, Mian; Hui, Lijian; Zhang, Huafeng; Gao, Ping
Abstract: Pluripotent stem cells are known to display distinct metabolic phenotypes than their somatic counterparts. While accumulating studies are focused on the roles of glucose and amino acid metabolism in facilitating pluripotency, little is known regarding the role of lipid metabolism in regulation of stem cell activities. Here, we show that fatty acid (FA) synthesis activation is critical for stem cell pluripotency. Our initial observations demonstrated enhanced lipogenesis in pluripotent cells and during cellular reprogramming. Further analysis indicated that de novo FA synthesis controls cellular reprogramming and embryonic stem cell pluripotency through mitochondrial fission. Mechanistically, we found that de novo FA synthesis regulated by the lipogenic enzyme ACC1 leads to the enhanced mitochondrial fission via (i) consumption of AcCoA which affects acetylation‐mediated FIS1 ubiquitin–proteasome degradation and (ii) generation of lipid products that drive the mitochondrial dynamic equilibrium toward fission. Moreover, we demonstrated that the effect of Acc1 on cellular reprogramming via mitochondrial fission also exists in human iPSC induction. In summary, our study reveals a critical involvement of the FA synthesis pathway in promoting ESC pluripotency and iPSC formation via regulating mitochondrial fission. Synopsis: Providing energy for cell growth and proliferation is the principal role of cellular glucose and amino acid metabolism in the support of stem cell pluripotency. However, anabolic fatty acid (FA) generation also appears to be essential for murine ESC maintenance and human iPSC reprogramming via mitochondrial dynamics. Cellular lipid levels and lipogenic enzyme expression are increased in pluripotent stem cells. De novo FA synthesis is required for maintenance of embryonic stem cell pluripotency and promotes mitochondrial fission. The lipogenic enzyme ACC1 stabilizes fission factor FIS1 by inhibiting its acetylation and degradation. ACC1 promotes somatic reprogramming of human fibroblasts to iPSCs via FIS1. Abstract : Lipid products and stabilization of fission factor FIS1 upon lipogenic consumption of acetyl‐CoA jointly impinge on mitochondrial dynamics to promote ESC maintenance and iPSC formation.